2020
DOI: 10.1002/hipo.23268
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐omics analysis suggests enhanced epileptogenesis in the Cornu Ammonis 3 of the pilocarpine model of mesial temporal lobe epilepsy

Abstract: Mesial temporal lobe epilepsy (MTLE) is a chronic neurological disorder characterized by the occurrence of seizures, and histopathological abnormalities in the mesial temporal lobe structures, mainly hippocampal sclerosis (HS). We used a multi-omics approach to determine the profile of transcript and protein expression in the dorsal and ventral hippocampal dentate gyrus (DG) and Cornu Ammonis 3 (CA3) in an animal model of MTLE induced by pilocarpine. We performed label-free proteomics and RNAseq from laser-mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 89 publications
(109 reference statements)
0
43
0
Order By: Relevance
“…By contrast, there was a downregulation in the WNT signaling pathway in the CA3. These findings also highlight the heterogeneity in the transcriptome and proteome of different hippocampal regions and areas (Canto et al, 2020).…”
Section: Pilocarpinementioning
confidence: 64%
See 3 more Smart Citations
“…By contrast, there was a downregulation in the WNT signaling pathway in the CA3. These findings also highlight the heterogeneity in the transcriptome and proteome of different hippocampal regions and areas (Canto et al, 2020).…”
Section: Pilocarpinementioning
confidence: 64%
“…In a very recent study performed by our group in 2020, we employed the pilocarpine model to broadly assess changes in the proteome and transcriptome of Wistar rats (Canto et al, 2020). We isolated different regions of the hippocampal formation, DG and CA3, as well as different areas (dorsal and ventral), using laser microdissection and determined their protein and transcriptional profiles-the transcriptomic study used next-generation sequencing, while the proteomic study used a label-free mass spectrometry approach.…”
Section: Pilocarpinementioning
confidence: 99%
See 2 more Smart Citations
“…Pathomorphological studies showed compromised neurogenesis and signi cant DG cell loss in RMTLE patients 10,11 and in vitro and animal model assays showed that the improper circuit control of DG-CA3 synapses leads to epilepsy, since DG acts as a "gate", protecting hippocampal circuits from overexcitation 12,13 . Multi-omics analyses performed in the pilocarpine rat model of MTLE suggested enhanced epileptogenesis in the CA3 region when compared to the DG, with most of the transcriptional and protein expression alterations occurring in CA3 14 . Additionally, the integrative study of CA3 transcriptional signatures and DG histopathology in hippocampal explants surgically obtained from RMTLE patients allowed our group, and others, to portrait the disease as a disturbed network of genegene interactions [15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 98%